Influence of midsole metatarsophalangeal stiffness on jumping and cutting movement abilities - Tinoco, N.; Bourgit, D.; Morin, J.-B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
The aim of this study was to determine whether increasing the stiffness of the shoe midsole supporting the metatarsophalangeal (MTP) joint could induce a better jumping and lateral cutting movement performance. Twelve young team-sports players used two different shoe models (commercialized), with different sole bending stiffnesses. Two tests were performed: a multi-directional (Multi-D) sprint test including rapid lateral braking and cutting movements, and a fatigue test including drop jumps (DJs) and countermovement jumps (CMJs) in pre- and post-fatigue conditions. A significant (p < 0.05) improvement was observed in the Multi-D test times with the stiffer midsole. Further, in fatigued conditions, the group with the stiffer midsole shoe showed a non-significant 9 per cent performance decrease in CMJs, while this decrease was higher and significant (16.1 per cent; p < 0.05) for the compliant midsole group. Compared with the stiffer midsole, the compliant midsole yielded a significant decrease in the jump performance, highlighting the fact that a higher MTP midsole stiffness helped subjects to limit the effects of fatigue on jumping performance. Therefore, a higher midsole MTP stiffness is associated with better performance in indoor-sport-specific movements including fatigued conditions, which could be explained by a preserved dynamic interaction with the ground in these specific sport situations.